Efficient carbon-Ferrier rearrangement on glycals mediated by ceric ammonium nitrate: Application to the synthesis of 2-deoxy-2-amino-C-glycoside - Ansari, Alafia A.; Reddy, Y. Suman; Vankar, Yashwant D. (Beilstein Journal of Organic Chemistry, 2014)
A carbon-Ferrier rearrangement on glycals has been performed by using ceric ammonium nitrate to obtain products in moderate to good yields with high selectivity. The versatility of this method has been demonstrated by applying it to differently protected glycals and by employing several nucleophiles. The obtained C-allyl glycoside has been utilized for the synthesis of a orthogonally protected 2-amino-2-deoxy-C-glycoside.
Keywords: C-glycosides; carbon-Ferrier rearrangement; ceric ammonium nitrate; 2-deoxy-2-aminoglycosides; Overman rearrangement